1968
DOI: 10.1084/jem.127.1.67
|View full text |Cite
|
Sign up to set email alerts
|

The Gastrointestinal Epithelium and Its Autochthonous Bacterial Flora

Abstract: Colonization of the gastrointestinal tract by bacteria of the normal flora was followed by bacteriological and special histological techniques in mice from several colonies. These histological techniques were designed to preserve the intimate associations that become established between particular strains of microorganisms and the epithelium of the mucosa of certain areas of the gut. The findings were as follows: 1. The various strains of bacteria of the normal flora became established in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
200
0
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(221 citation statements)
references
References 8 publications
18
200
0
1
Order By: Relevance
“…Significant QTL were detected for Helicobacter, but no QTL were identified for Lactobacillus (Table S1). Lactobacilli form dense cell layers on the murine forestomach epithelium, and its isolates' adherence phenotypes have been shown to be host-specific (24,25); L. reuteri even comprises host-adapted subpopulations (26). This degree of host adaptation at the species level and below, and the fact that no QTL were detected at the genus level, led us to speculate that it may be precisely at the lower taxonomic ranks that host genetic control over Lactobacilli is exerted.…”
Section: Resultsmentioning
confidence: 96%
“…Significant QTL were detected for Helicobacter, but no QTL were identified for Lactobacillus (Table S1). Lactobacilli form dense cell layers on the murine forestomach epithelium, and its isolates' adherence phenotypes have been shown to be host-specific (24,25); L. reuteri even comprises host-adapted subpopulations (26). This degree of host adaptation at the species level and below, and the fact that no QTL were detected at the genus level, led us to speculate that it may be precisely at the lower taxonomic ranks that host genetic control over Lactobacilli is exerted.…”
Section: Resultsmentioning
confidence: 96%
“…[1][2][3][4] Studies in gnotobiotic animals have shown that association of germ-free rodents with single bacterial species has a profound impact on the anatomical, physiological, and immunological development of the host, including effects on epithelial cell functions and the gut-associated lymphoid tissue. [5][6][7] The complex homeostasis between non-pathogenic intestinal micro-organisms and the host is an intriguing immunological paradox as the normal mucosal immune system acquires tolerance (hyporesponsiveness) to the enteric microbiota, while protective cell-mediated and humoral immune responses to enteropathogens are maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results a new genus and species, Mucispirillum schaedleri gen. nov., sp. nov., is proposed in honour of Russell Schaedler, one of the early pioneers of the study of the bacteria of the intestinal tract of mammals and the first to isolate a member of this genus (ASF 457) as part of the altered Schaedler flora Savage et al, 1968;Schaedler et al, 1965; Dewhirst et al, 1999). …”
mentioning
confidence: 99%